DETERMINATION OF EFFECTIVE DIRECTIONS AND CRITERIA OF INNOVATIVE WORK IN THE FIELD OF SOLAR ENERGY - Pundiev, V.; Shevchuk, V.; Marchenko, N. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2021)
An overview of the state and development in the world of the solar cell industry as a basic unit of photovoltaic modules, which are produced and are at the research stage to date. The article focuses on the four most well-known types of photovoltaic modules that use solar cells, taking into account both certain design differences in their manufacture and technical and economic costs, features of operation and disposal after decommissioning of modules. A method of analysis of photovoltaic modules using the method of pairwise comparisons has been developed and criteria have been established that take into account their technical and economic indicators and market factors (per unit of installed capacity), namely: cost; module weight; мodule efficiency; environmental friendliness of module disposal after failure or termination of service life; features of degradation of each separate type of the module. The analysis of basic segments of types of photovoltaic modules is carried out and integrated estimations for each segment are defined. The highest integrated score was received by the segment of modules made on the basis of single-crystal silicon, and the lowest - the segment of modules made on the basis of СdTe. The second and third places were practically shared by modules based on amorphous silicon and based on perovskite structures. According to the results of this analysis, it is proposed to focus investments on the development of the photovoltaic industry in the segment of modules that use tandem solar cells based on single-crystal silicon and perovskite structures. Factories for the production of solar cells based on crystalline silicon exist in Ukraine, and the development and manufacture of perovskite structures must be developed. Ref. 9, tab. 5, fig. 1.